Formula Alamin: Alamtologi Communication - Muhammad Aminullah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
This study is very important as a solution to explain the proper communication and how to implement the right communication process in achieving harmony values for all elements related to humans. Unlimited communication between human relations, but also need to understand the form of relations with other than humans. The methodology used in this study is based on an approach that was awakened in the discipline of ALAMTOGI namely the XYZ formula. The XYZ formula explains all the life processes that are manifest are still subject to the XYZ relationship. X as the executor, namely human, Z as the media, namely the element of nature, and Y as the creator, namely constructor Z and X. The result of research that is harmonious communication is communication carried out by means of legal agreement, starting from process planning, process implementation to process achievement. Legal accuracy, that is, every action taken by X in using Z, must understand the value of prosperity possessed by element Z. Planning the communication process can be carried out in four stages, namely the accuracy of planning, preparation of planning tools, willingness of planning tools and willingness to implement the implementation process . The right communication is to be able to produce certainty based on the certainty of the process. However, if communication is based on perceptions of the process, then it certainly produces predictions of results. This is what is called harmony communication.